A proposed method for assessing the quality of sealants – the CCC Sealant Evaluation System - Deery C, Fyffe HE, Nugent ZJ, Nuttall NM, Pitts NB (Blackwell Synergy, 2001)
The aim of this paper is to introduce the C (colour) C (coverage) C (caries) Sealant Evaluation System and to present results of its use on a sample of adolescent patients in Scotland. Methods: Baseline data are presented from a 3-year prospective study in general dental practices across Scotland. Subjects were examined under standardised conditions by one trained and calibrated examiner.